Coumarin 545: an emission reference dye with a record-low temperature coefficient for ratiometric fluorescence based temperature measurements1. Issue 4 (21st February 2015) - Mao, Deqi; Liu, Xiaogang; Qiao, Qinglong; Yin, Wenting; Zhao, Miao; Cole, Jacqueline M.; Cui, Jingnan; Xu, Zhaochao
<x xml:space="preserve">Abstract</x> The emission intensities of coumarin 545 solution exhibit a low temperature dependence, with a record-low temperature coefficient of only ∼0.025% per °C.